2021
DOI: 10.1038/s41598-021-93314-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of infection complications after trauma differs according to trauma severity

Abstract: The impact of infection on the prognosis of trauma patients according to severity remains unclear. We assessed the impact of infection complications on in-hospital mortality among patients with trauma according to severity. This retrospective cohort study used a nationwide registry of trauma patients. Patients aged ≥ 18 years with blunt or penetrating trauma who were admitted to intensive care units or general wards between 2004 and 2017 were included. We compared the baseline characteristics and outcomes betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…We also found that older trauma patients experienced longer in-hospital LOS, which is in line with the results reported by other authors [38][39][40] . This could be related to the higher incidence of complications in this population [41][42][43][44] . However, we cannot rule out that these complications may also be the consequence of longer LOS.…”
Section: Discussionmentioning
confidence: 92%
“…We also found that older trauma patients experienced longer in-hospital LOS, which is in line with the results reported by other authors [38][39][40] . This could be related to the higher incidence of complications in this population [41][42][43][44] . However, we cannot rule out that these complications may also be the consequence of longer LOS.…”
Section: Discussionmentioning
confidence: 92%
“…We also found that older trauma patients experienced longer in-hospital LOS, which is in line with the results reported by other authors [ 38 40 ]. This could be related to the higher incidence of complications in this population [ 41 44 ]. However, we cannot rule out that these complications may also be the consequence of longer LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the patient was transferred to the ICU on October 5, 2021 due to suspected traumatic wet lung infections and persistent low blood oxygen concentration. Greater of injury severity is associated with the higher risk of infections ( 30 ). A previous study of 5,500 patients following trauma revealed that the injury severity score in the infected group was significantly higher compared with that of the non-infected group ( 31 ).…”
Section: Discussionmentioning
confidence: 99%